The classification of Flabellochromus and Dumbrellia (Coleoptera: Lycidae) with descriptions of two new species of Calochromus from the Sundaland Region - Motyka, Michal; Bocak, Ladislav (Zootaxa, 2015)
The adults of Calochromini with male flabellate antennae were studied. Two new Calochromus Guérin-Méneville, 1833 species with flabellate antennae, C. kelantanensis spec. nov. and C. harauensis spec. nov. are described. Dumbrellia Lea, 1909 (Calochromini) is proposed as a new junior synonym of Plateros Bourgeois, 1879 (Lycinae: Platerodini). Flabellochromus Pic, 1925 is transferred to Calochromus from synonymy with Dumbrellia based on the similar shape of the pronotum. Consequently, Calochromus lamellatus Kleine, 1926, comb. nov. from Sarawak and Flabellochromus pallidus Pic, 1925, comb. nov. (=Calochromus (Flabellochromus) pallidus Pic, 1925) from Luzon are returned to Calochromus. New combinations are proposed for three Australian species previously classified in Dumbrellia: Plateros brevicornis (Lea, 1898), comb. nov. (=Calochromus brevicornis Lea, 1898), P. pilosicornis (Lea, 1898), comb. nov. (=C. pilosicornis Lea, 1898) and P. melancholica (Lea, 1921), comb. nov. Plateros barronensis nom. nov. is proposed to replace Plateros pilosicornis (Lea, 1898), a junior secondary homonym of P. pilosicornis (Blanchard, 1853) (=Lycus pilosicornis Blanchard, 1853).